2016
DOI: 10.1242/dev.134999
|View full text |Cite
|
Sign up to set email alerts
|

A gene regulatory network for apical organ neurogenesis and its spatial control in sea star embryos

Abstract: How neural stem cells generate the correct number and type of differentiated neurons in appropriate places remains an important question. Although nervous systems are diverse across phyla, in many taxa the larva forms an anterior concentration of serotonergic neurons, or apical organ. The sea star embryo initially has a panneurogenic ectoderm, but the genetic mechanism that directs a subset of these cells to generate serotonergic neurons in a particular location is unresolved. We show that neurogenesis in sea … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 32 publications
3
50
1
Order By: Relevance
“…It is not known whether this mechanism exists in sea star, but expression of wnt5 , nk1 and pax2/5/8 is expressed similarly in the two taxa (McCauley et al, ; Yankura, Martik, Jennings, & Hinman, ). The remaining more anterior ectoderm is a Wnt negative zone, and therefore when cWnt signaling is experimentally abrogated, the resultant embryos fail to gastrulate, do not develop endoderm or mesoderm, and form permanent blastulae in which the neuroectoderm is expanded and unpatterned (Cheatle Jarvela, Yankura, & Hinman, ; Logan et al, ; Range, Angerer, & Angerer, ; Yaguchi, Yaguchi, & Burke, ).…”
Section: The Animal Vegetal Axis and The Specification Of The Animal mentioning
confidence: 99%
See 3 more Smart Citations
“…It is not known whether this mechanism exists in sea star, but expression of wnt5 , nk1 and pax2/5/8 is expressed similarly in the two taxa (McCauley et al, ; Yankura, Martik, Jennings, & Hinman, ). The remaining more anterior ectoderm is a Wnt negative zone, and therefore when cWnt signaling is experimentally abrogated, the resultant embryos fail to gastrulate, do not develop endoderm or mesoderm, and form permanent blastulae in which the neuroectoderm is expanded and unpatterned (Cheatle Jarvela, Yankura, & Hinman, ; Logan et al, ; Range, Angerer, & Angerer, ; Yaguchi, Yaguchi, & Burke, ).…”
Section: The Animal Vegetal Axis and The Specification Of The Animal mentioning
confidence: 99%
“…In sea stars, the expression of orthologous Wnt and Fzl genes is similarly positioned along the AP axis (McCauley et al, ). Foxq2 is expressed in the anterior most ectoderm, where it is needed to activate the expression of dkk3 , and is necessary for the formation of serotonergic neurons (Cheatle Jarvela et al, ). These data are therefore consistent with sea star APDs being established through interplay between Wnt and Wnt antagonists although the specific interactions observed in sea urchins have not been tested.…”
Section: The Animal Vegetal Axis and The Specification Of The Animal mentioning
confidence: 99%
See 2 more Smart Citations
“…The foxQ2 expression in the six3/6 ‐free region has also been reported in protostomes (Kitzmann et al, ; Marlow et al, ; Martín‐Durán et al, ; Santagata et al, ). In addition, a recent study of embryos of another echinoderm (starfish) has reported that Six3 knockdown‐embryos still express foxQ2 at the gastrula stage (Cheatle Jarvela, Yankura, & Hinman, ), although it is possible that the regulatory relationship was modified after the diversification of sea urchin and starfish. In summary, it is still unclear how the expression of foxQ2 is positively regulated and maintained in the anterior neuroectoderm.…”
Section: Introductionmentioning
confidence: 99%